2006
DOI: 10.21000/jasmr06021122
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Versus Actual Water Quality at Hardrock Mine Sites: Effect of Inherent Geochemical and Hydrologic Characteristics

Abstract: The Environmental Impact Statements (EISs) for 70 large modern-era hardrock mines in the United States were reviewed to determine their predicted impacts to water resources. EIS predictions were then compared to actual water quality conditions for 24 of the 70 mines (case studies), and the effects of geochemical characteristics and hydrologic conditions on operational water quality were evaluated. Nearly all case study mines with close proximity to water resources and moderate to high potential for acid draina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Luo and Sophocleous [10] used HYDRUS -1D to estimate groundwater flow values ranging from -3.5 x 10 -8 to 3.5 x 10 -8 m 3 s -1 with a coefficient of determination (r 2 ) value of 0.75 between simulated and measured groundwater flow in an agricultural field located in Shandong province, China. A number of other numerical groundwater models (e.g CPFLOW, MODFLOW, SUTRA, HYDRUS and FEFLOW) [11] have been shown to successfully predict groundwater flow in varying hydrogeologic settings. Despite technological progress in modeling, previous authors indicated that improved model accuracy requires proper parameterization, emphasizing the need for higher resolution (spatial and temporal) field observations [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Luo and Sophocleous [10] used HYDRUS -1D to estimate groundwater flow values ranging from -3.5 x 10 -8 to 3.5 x 10 -8 m 3 s -1 with a coefficient of determination (r 2 ) value of 0.75 between simulated and measured groundwater flow in an agricultural field located in Shandong province, China. A number of other numerical groundwater models (e.g CPFLOW, MODFLOW, SUTRA, HYDRUS and FEFLOW) [11] have been shown to successfully predict groundwater flow in varying hydrogeologic settings. Despite technological progress in modeling, previous authors indicated that improved model accuracy requires proper parameterization, emphasizing the need for higher resolution (spatial and temporal) field observations [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The ABA test procedure determines the acid-producing and acid-neutralizing potentials of a test material (Sobek et al 1978). AcidBase Accounting is a highly projected and favoured geochemical characterisation method with a relatively short turn-around time; the procedure is very cost effective as compared with other methods (US EPA 1994; Maest et al 2005). By reason of the above qualities, ABA is often recommended for use at the exploration phase of mining projects for early decision making (McKenna et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…That notwithstanding, acurate prediction is recognized by both industry and government as a critical requirement for mines permitting and long-term operation (Maest et al 2005;Skousen and Ziemkiewicz 1996;MEND 2001).…”
Section: Introductionmentioning
confidence: 99%